Factors that Distinguish Parenting Styles of Working Mothers with Grandmothers in Children Aged Under 5-6 Years - Iradatul Hasna (Yayasan Adra Karima Hubbi, 2024)
This research is motivated by the differences in parenting styles given by working mothers with grandmothers, This difference is certainly influenced by various factors. The purpose of this study was to analyze the factors that distinguish the parenting style of working mothers with grandmothers. This study uses a type of qualitative research with a case study method, the population of this study is all mothers and grandmothers who live in the same house, and the data source is selected by purposive sampling, which is taking samples according to the criteria that the research expects and data analysis techniques using data reduction measures, in data play and data verification. There are three parenting styles applied by parents in parenting their children in everyday life. These parenting styles include democratic parenting, authoritarian parenting, and permissive parenting. The formation of parenting is influenced by age, parental involvement, husband-wife relationships, education and previous experience, and parental stress. The formation of democratic parenting in Mrs. H, Mrs. SEY, Mrs. YN and Mrs. ER is influenced by the mature age of the mother, and the involvement of a large father and grandmother. In authoritarian parenting, TD's mother is influenced by the absence of father's involvement, a lot of work stress, and divorced husband and wife relationships, while SR's grandmother's authoritarian parenting style is influenced by high-stress levels due to parenting eight grandchildren and previous parental upbringing experiences that apply authoritarian parenting. Permissive parenting in grandmothers S, AS, Y and YZ is influenced by old age, low education and the experience of their parents who previously applied permissive parenting.